The Relationship between Socioeconomic Status and The Patterns of Food and Nutrition Consumption of the Household in Rural Areas of Muaro Jambi Regency - Suandi, Suandi; Damayanti, Yusma (KOMUNITAS: International Journal of Indonesian Society and Culture, 2016)
The objective of this research is to analyze the relationship between family socioeconomic status and nutritional adequacy rate in rural areas of Muaro Jambi, Jambi Province. The study design was cross-sectional. The study was conducted in rural areas of Muaro Jambi, Jambi province by selecting three districts, namely: district of Sekernan, Kumpeh Ulu, and Mestong. The research was conducted from July to December 2014. The sample was 180 families and were taken by purposive and simple random sampling. Data were tested by descriptive and Product Moment Correlation. The results showed that consumption of food and nutrition in the study area is almost close to the recommended nutrition adequacy standard. Results of the analysis showed that the variables of household head age, family size and income are positively and significantly correlated to energy and protein consumption adequacy of the family, while the factor of household head education was unrelated.